A Funded Pension System with Endogenous Retirement - Kobayashi, Wataru; Takahata, Junichiro (Asian Journal of Economic Modelling, 2022)
This study employs an overlapping generations model to analyze the effect of public pension levels on economic variables when the labor supply of the elderly is determined endogenously. This paper focuses on the effects of a funded scheme on the economy as well as a pay-as-you-go (PAYG) scheme. First, the impact of the expansion of public pensions on the capital–labor ratio is analyzed. It is shown that the expansion of a funded pension increases the capital–labor ratio, which is contrasted with the fact that the PAYG pension is neutral to capital–labor ratio. Next, the impact of public pensions’ introduction on steady-state economic welfare is evaluated. The introduction of a PAYG pension will improve economic welfare when the population growth rate is higher than the interest rate, while the introduction of a funded pension will improve economic welfare when the population growth rate is lower than the interest rate.